« L’eau qui atteint la mer est une eau perdue » : anthropocentrisme et dégradation des écosystèmes aquatiques - Frédéric Julien (VertigO, 2010)
The degradation of the planet’s freshwater ecosystems constitutes one of the main dimensions of the “global water crisis”. As a result of human activity, this degradation is ultimately allowed to occur by an ethic that only takes people into account and therefore reduces water and freshwater ecosystems to the status of resources to be exploited. Given the impact of humanity’s relationship with nature on water governance, there is a need to rethink the current anthropocentric ethic and to move beyond it. Such an ethical accomplishment would require that Homo sapiens accept limits to their freedom of action in the struggle for existence. These limits, it is suggested, could be based on a reverence for water as a life support system.